Penyelesaian Sengketa Pelanggaran Disiplin Pegawai Negeri Sipil oleh Pengadilan Tata Usaha Negara Kupang - Weli Phelpina Elisabet Malubala; Yohanes G. Tuba Helan; Norani Asnawi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The purpose of this research is to analyze the settlement of disputes over violations of civil servant discipline by the Kupang State Administrative Court. This research method is normative legal research. The location of this research was conducted at the Kupang State Administrative Court Office. The type of data used in this research is normative research, the data used is secondary data. Data collection techniques that will be carried out are through literature studies and also interviews with sources, namely judges. Data processing techniques in this research conduct studies or analyses in a descriptive juridical and prescriptive juridical manner on legal materials. The result of this research is that the types of employment disputes examined, decided and resolved by PTUN Kupang are generally 2 (two) types, namely disputes due to disciplinary punishment and disputes due to rotation, mutation / promotion and / or filling positions. The subject of litigation specifically for employment disputes is an active and/or former civil servant acting as a plaintiff against a state administrative body or official. The state administrative decision being challenged or the object of the dispute is a decision relating to disciplinary punishment or rotation, transfer/promotion or filling a position against a Civil Servant. The procedure or process of examining civil service disputes at the PTUN is basically the same as examining state administrative disputes in general, namely through 3 (three) processes, namely, the Administrative Process, the Examination Process and the Trial Process, with an examination using a choice of procedural law, namely the Ordinary Procedure, Fast Procedure or Short Procedure.